A quantitative kinetic model for the fast and isothermal hydrothermal liquefaction of Nannochloropsis sp. (August 2016) - Hietala, David C.; Faeth, Julia L.; Savage, Phillip E.
Highlights: Conducted comprehensive kinetic study of microalgal HTL product distribution. Developed microalgal HTL kinetic model valid over short timescales (10 s–10 min). 46 wt% biocrude yield predicted after 1 min at an isothermal temperature of 400 °C. Model demonstrates trade-offs between biocrude quantity and aqueous phase recovery. Abstract: Hydrothermal liquefaction (HTL) is a technology for converting algal biomass into biocrude oil and high-value products. To elucidate the underlying kinetics for this process, we conducted isothermal and non-isothermal reactions over a broad range of holding times (10 s–60 min), temperatures (100–400 °C), and average heating rates (110–350 °C min −1 ). Biocrude reached high yields ( ⩾ 37 wt%) within 2 min for heat-source set-point temperatures of 350 °C or higher. We developed a microalgal HTL kinetic model valid from 10 s to 60 min, including significantly shorter timescales (10 s–10 min) than any previous model. The model predicts that up to 46 wt% biocrude yields are achievable at 400 °C and 1 min, reaffirming the utility of short holding times and "fast" HTL. We highlight potential trade-offs between maximizing biocrude quantity and facilitating aqueous phase recovery, which may improve biocrude quality.